Formação integral: um estudo da construção do processo de acompanhamento dos estudantes na dimensão socioemocional na 1ª série do ensino médio - Fávero, Mariana Consulmagno (Universidade do Vale do Rio dos Sinos, 2022)
This research has as theme the construction of the process of personalized follow up to the students, mainly in relation to the socio-emotional dimension, to assure their integral formation. The problematizing question is about: “how does the follow-up process take place under the eyes of the advisors of Unit III and of the students of the 1st grade of High School and how can we build a follow-up proposal in the socio-emotional dimension ensuring integral formation? Its general aim is to analyze this process from the perspective of Unit III guidance team and the students themselves, to propose a follow-up construction in the socio-emotional dimension, in order to promote integral formation. The research was carried out at Colégio dos Jesuítas, which belongs to the Jesuit Education Network. Its participants are 1st grade High School students and Unit III advisors. The methodology adopted was the case study, with a mixed approach (quantitative and qualitative) and with the application of a questionnaire to the students of the 1st grade of High School using questions with a Likert scale and structured interview for the advisors. Descriptive statistics and content analysis proposed by Bardin (2011) were used for data analysis. With the result of this research, it is observed that Colégio dos Jesuítas has been improving the model of monitoring students. Its differential lies in innovating to educate and in care and development beyond the academic scope in search of integral formation. However, it is possible to mention some points of attention that were identified and worked on in the intervention proposal. Finally, this study presents as a tool for monitoring the socio-emotional dimension a proposal for anamnesis with students that comprises the 5 Cs of Ignatian Pedagogy related to the five domains of emotional intelligence, namely: knowing your emotions/being aware, dealing with emotions/being committed, motivating yourself/being creative, recognizing emotions in others/being compassionate, dealing with relationships/being competent. Therefore, a schedule of training and pedagogical reflection was also proposed for the advisors, emphasizing the work in recognizing the construct of the mission, vision and institutional values and means to assure integral learning in the light of PEC, with the development of the affective, spiritual religious, ethical, aesthetic, cognitive, corporeal and sociopolitical dimensions (PEC, 2021).
Keywords: Socioemocional; Formação integral; Aprendizagem; Acompanhamento; Socioemotional; Integral formation; Learning; Follow-up; ACCNPQ::Ciências Humanas::Educação